PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DIREKTORAT JENDERAL PENDIDIKAN ANAK USIA DINI, PENDIDIKAN DASAR, DAN PENDIDIKAN MENENGAH KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET DAN TEKNOLOG - Darmawan, Eric Geovani (Taksasila Edukasi Insani, 2024)
ABSTRACTThe purpose of this research is to determine the influence of organizational culture and work environment on employee performance. This research uses a survey method with a questionnaire as the instrument. The respondents for this research were 50 employees at the Ministry of Education, Culture, Research and Technology. The sampling process uses a non-probability sampling technique using an associative quantitative approach using primary data. The data analysis technique used is SPSS Version 20.These results show that organizational culture has a positive effect where the value of tcount ttable (2.568 2.011), and is not significant with a value of sig. greater than 0.05 or 0.13 0.05 or 5% of Employee Performance. The work environment has a positive effect where the value of tcount ttable (4.013 2.011) and is significant with a value of 0.000 0.05 or 5% on employee performance. Together, Organizational Culture (X1) and Work Environment (X2) have a positive relationship and from the results of the F test they simultaneously have a significant effect on employee performance with a value of Fcount Ftable (32,966 3.195) with a significant value of 0.000 which is smaller than 0, 05 or 5% of Employee Performance.Keywords: Organizational Culture, Work Environment, Employee Performance